Effect of natural aging time on anisotropic plasticity and fracture limit of Al7075 alloy. (June 2022) - Jung, Seon-Ho; Bae, Gihyun; Kim, Minki; Lee, Jongsup; Song, Junghan; Park, Namsu
Abstract: Numerical approaches for fracture modeling have been proposed for various metallic materials, including high-strength steels and aluminum alloys. However, the quantitative relationship between the Portevin–Le Chatelier (PLC) effect and the fracture initiation has not been yet fully explored, considering the influence of the natural aging time (NA) on the material deformation behavior. To address this gap, this study investigated the PLC effect on the anisotropic plasticity and fracture limit of Al7075 alloy according to the natural aging time. Aging behavior and PLC effects are experimentally evaluated through uniaxial tensile and fracture tests using the 3D digital image correlation method. The natural aging-dependent PLC effect is tracked in the visualization of the strain rate map and thickness strain distributions with plastic deformation. Variations in the anisotropic plasticity are captured using Barlat's YLD2000‐2d anisotropic yield function at different natural aging times, and fracture envelopes that cover general 3D stress states are identified based on the Lou–Huh ductile fracture criterion. A natural aging-dependent fracture modeling approach is proposed to predict the influence of natural aging on the fracture limit transition. Finally, the strain- and stress-based fracture forming limit diagrams, including their corresponding magnitude of the stress vector, are represented. The results reveal that no general trend for the natural aging-dependent fracture limit based on the strain metric is observed, whereas the fracture limit based on the stress metric tends to increase with natural aging in various loading conditions. Graphical Abstract: ga1 Highlights: PLC effect on anisotropic plasticity and fracture limit of Al 7075 alloy studied. Natural aging leads to suppression of the serrated stress fluctuation. Propsoed a fracture modeling approach based on natural aging time. Predicted influence of natural aging on the ductility limit transition. Fracture limit based on the stress metric increases with natural aging time.